Toxicity and Anti-Inflammatory Effects of Agave sisalana Extract Derived from Agroindustrial Residue - Luisa Taynara Silvério da Costa; Julia Amanda Rodrigues Fracasso; Lucas Pires Guarnier; Gustavo Reis de Brito; Daniel Baldini Fumis; Renata Aparecida de Camargo Bittencourt; Aimée Maria Guiotti; Débora de Barros Barbosa; Isabel Cristina Cherici Camargo; Edislane Barreiros de Souza; Pedro de Oliva Neto; Lucinéia dos Santos (Plants, 2023)
Background: In several countries, the leaf juice of Agave sisalana (also known as sisal) is widely used topically, especially as an antiseptic, and orally for the treatment of different pathologies. However, in Brazil, which is the largest producer of Agave sisalana, its residue, which represents the majority of its weight, has been thrown away. For this reason, the determination of the pharmacological and toxicological potentials of sisal residue and its possible therapeutic use is seen as a way to contribute to the sustainable development and social promotion of the largest producer of sisal in Brazil, the interior of Bahia State, which is among the poorest areas in the country. Given the scarcity of available scientific studies on the pharmacological and toxicological properties of sisal residue juice, this study aimed to promote the acid hydrolysis of this juice to potentiate the anti-inflammatory effect already described in the literature. Furthermore, it aimed to evaluate the toxicological profile of the hydrolyzed extract (EAH) and to determine its acute toxicity, as well as its side effects on the reproductive aspects of rats. Method: The anti-inflammatory effect of EAH was evaluated in vitro using the induction of hemolysis by hypotonic solution and in vivo in rats using the carrageenan-induced paw edema test and the xylene-induced ear edema test. The acute toxicity, resulting from a single-dose administration, was investigated for some manifestation of toxic symptoms related to motor control and consciousness in rats. At a concentration of 100 mg/kg, by repeated doses, the reproductive toxicity effects of EAH in rats were assessed. Results: In vitro anti-inflammatory activity was positive using the human red blood cell membrane stabilization method. In both in vivo tests used to assess the anti-inflammatory activity, EAH (at three doses) significantly inhibited edema when compared to the control group. At a dose of 50 mg/kg, EAH exhibited a greater effect than indomethacin, a nonsteroidal anti-inflammatory drug with known activity. In vivo toxicological studies have shown that EAH does not present toxic effects when administered orally in a single dose, up to 1000 mg/kg. Finally, EAH promoted a gonadotoxic effect and increased the embryonic mortality rate after implantation. Conclusions: It is suggested that the anti-edematogenic effect of the acid hydrolysis extract from sisal juice is due to the high concentration of steroidal sapogenins. Therefore, this extract can be considered a potential new anti-inflammatory or even an important sapogenin source for the development of steroidal glucocorticoids. However, further studies are needed to elucidate the chemical composition of sisal juice. Regarding toxicology studies, EAH did not show cytotoxic and clastogenic potentials, but it presented a powerful reproductive toxic effect in rats.